Self-deprecatory humor on TV cooking shows. (September 2017) - Matwick, Keri; Matwick, Kelsi
Abstract: Humor and joking are instruments through which social control is exerted and through which self-identity is displayed. A form of self-disclosure, humorous self-deprecation is self-directed critique done in a humorous way to minimize possible value judgments the self-revealing information might provoke. While much of humor has been examined in the context of natural conversation or between participants in the media, little attention has been given to humor performed individually in a pseudo-interactional context. A pragmatics approach shows how humorous self-deprecations of celebrity chefs in single-hosted how-to-cook cooking shows serve to entertain, build solidarity, and construct authenticity. We further argue that self-deprecation protects the speaker from criticism and also promotes hegemonic values of what is appropriate and inappropriate gendered behavior. Highlights: Self-deprecation creates a performance of being ordinary. Self-deprecation builds rapport between celebrities and their audience. Self-deprecation has moral implications, especially in relation to gender and food.